2022
DOI: 10.3389/fimmu.2022.999534
|View full text |Cite
|
Sign up to set email alerts
|

An update on the interaction between COVID-19, vaccines, and diabetic kidney disease

Abstract: Up to now, coronavirus disease 2019 (COVID-19) is still affecting worldwide due to its highly infectious nature anrapid spread. Diabetic kidney disease (DKD) is an independent risk factor for severe COVID-19 outcomes, and they have a certain correlation in some aspects. Particularly, the activated renin–angiotensin–aldosterone system, chronic inflammation, endothelial dysfunction, and hypercoagulation state play an important role in the underlying mechanism linking COVID-19 to DKD. The dipeptidyl peptidase-4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…A review study published on 20 October 2022 10 examined the correlation between COVID-19 and DKD and the potential mechanisms for elevated blood glucose levels following vaccination. A study conducted in a German community hospital analyzed a cohort of 75 COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review study published on 20 October 2022 10 examined the correlation between COVID-19 and DKD and the potential mechanisms for elevated blood glucose levels following vaccination. A study conducted in a German community hospital analyzed a cohort of 75 COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…To Summarize, article 10 emphasizes that the connection between COVID-19 and DKD is intricate and bidirectional, with RAAS activation, chronic inflammation, and endothelial dysfunction being the key factors connecting the two conditions. Endothelial dysfunction leads to a procoagulant and anti-fibrinolytic state, whereas SARS-CoV-2 disrupts the glucose-insulin axis, causing oxidative stress and worsening DKD.…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that 16.6% of the participants tested positive for COVID-19, which is higher when compared to 7.5% in a study conducted by Nachimuthu et al but around equal to 17.1% in the study by Tourkamani et al whereas 11% and 8% prevalence of diabetes in patients with COVID-19 in studies by Singh et al and Yang et al respectively. [7][8][9][10] In India, 70% of the total population is fully vaccinated and almost 16% of the total population has also received the 3 rd precautionary dose. 2 Our study found that 91.3% of subjects received at least one dose, which is far much higher than the 21.5% found in the study by Nachimuthu et al in 2021 and 25.2% in Chinese patients in the study by Duan et al in 2022, but nearly equal to 84.8% found in study by Tourkamani et al Saudi Arabia in 2022.…”
Section: Discussionmentioning
confidence: 99%